Students’ Perception toward the Use of Google Site as English Academic Diary - Dian Puspita; Sandi Nuansa; Annisaa Toya Mentari (Community Development Journal : Jurnal Pengabdian Masyarakat, 2021)
As technology has been developing, it influences all aspect of human’s life, including learning process in education. There are a lot of online platforms that can be used to facilitate learning and enhance students’ understanding on the subject. One community service activity was done to make the innovative use of technology, Google Site, as Academic Diary for English subject. This paper was aimed to describe students’ perception toward the use of Google Site as online Academic Diary. Twenty students participated in this activity, and a questionnaire was distributed to find out their perception toward the use of Google Site. The result showed that most students received the positive perception, especially at Perception of Digital Technology and the use of Google Site.